THE CRISTAL WITH PARTICIPATE OF THE XENOMORPHIC SURFACE AND THE VARIANCE OF FACE SYSTEM - L.A., Admakin (International Journal of Engineering Technologies and Management Research, 2025)
Geometric crystallography studies the external form of a crystal, formed by a combination of geometric planes - reticular faces. This form of natural crystals can vary from simple forms, with the smallest number of faces, to polyhedral, with a certain number of faces. Such crystals are called idiomorphic, since they are geometric crystalline polyhedra. Faces that differ in reticular densities are called reticular, and faces multiplied by symmetry elements are called identical. The set of these faces is called a faceted form. By symmetry operations, the faceted form is transformed into a form consisting of only reticular faces. Such a form is called a faceted system. However, natural crystals are often subject to mechanical and (or) chemical dislocations and a xenomorphic surface appears in the faceted form. The faces can be partially or completely destroyed, and the crystalline polyhedron becomes unclosed, a greater or lesser part of the surface of its previously euhedral crystal becomes xenomorphic, and the face system consisting of the preserved reticular faces and the xenomorphic surface is combined; in it, the xenomorphic surface closes the crystalline polyhedron. Such crystals are hypidiomorphic. Xenomorphization, as a process of destruction of reticular faces, changes the thermodynamic state of the crystal. However, in geometric crystallography this surface is considered as a crystal defect, and the hypidiomorphic crystal is still studied as euhedral, its equilibrium is estimated, which is unjustified, since the xenomorphic surface is characterized by its own surface tension and, in essence, plays the role of an independent faceted surface. The role of the xenomorphic surface in the variability of such crystals was studied for the first time. Variance functions are obtained for different states of a face system involving a xenomorphic surface.